Enhancing Customer Loyalty Through the 7P Marketing Mix and the Mediating Role of Customer Satisfaction in Jago Coffee - Adinda Kirana Murni Siregar; Retnaningsih Retnaningsih; Anggi Mayang Sari (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: The growth of urban coffee consumption has intensified competition in Indonesia’s mobile coffee service industry, requiring companies to strengthen customer satisfaction and loyalty.Purpose: This study examines the influence of the 7P marketing mix on customer loyalty through the mediating role of customer satisfaction at Jago Coffee.Design/methodology/approach: A mixed-method approach was employed using SEM-PLS analysis based on questionnaires from 162 Jago Coffee consumers and supported by in-depth interviews in Jakarta.Findings/Result: The results indicate that all dimensions of the 7P marketing mix significantly and positively influence customer loyalty through customer satisfaction. Among the 7P elements, physical evidence showed the strongest contribution, while product and promotion demonstrated relatively lower effects. Customers particularly valued product quality, service efficiency, and digital convenience.Conclusion: An integrated 7P marketing mix supported by customer satisfaction plays an important role in strengthening customer loyalty in mobile coffee services.Originality/value (State of the art): This study provides a comprehensive model integrating the 7P marketing mix with customer satisfaction as a mediating variable in the mobile coffee business context an area that remains underexplored in the Indonesian F&B industry. Keywords:  customer loyalty, customer satisfaction, marketing mix 7P, SEM-PLS